Sistem Pakar Berbasis Website Untuk Diagnosis Stunting Balita Dengan metode Forward Chaining - ., Winarti; Putra, Wahyu Fikri Zeni; Maghfirohc, Nurus Danti; Nadila, Andin Rachma; ., Juliah; Fizaruddin, Mukhammad Amar; Sanjaya, Bagus Hadi (Jurnal Sains dan Teknologi (JSIT), 2025)
Artificial intelligence is the computer science sector which facilitates computers in performing tasks traditionally performed by humans. One of the interesting applications of ai is a system of experts, designed to mimic an expert's thinking and knowledge. In this study, a web-based expert system was developed to diagnose stunted potential in children of an early age by employing advanced methodologies of chaining. The purpose of this system is to increase public awareness and help parents recognize early stunting signs, thus enabling timely intervention. The system is developed with a cascading approach to ensure that each stage of development is implemented by a planned approach. Test results show that the system has a high diagnostic accuracy level, so it can be relied upon as an aid in a stunted risk assessment.